2003
DOI: 10.1183/09031936.03.00306302
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal suppression from high-dose inhaled fluticasone propionate in children with asthma: Fig. 1.—

Abstract: This cross-sectional study was designed to examine the prevalence of adrenocortical suppression in children with asthma treated with high-dose inhaled fluticasone propionate (FP).Children and adolescents (n=50) with asthma, treated with inhaled FP at a dose of o1,000 mg a day for o6 months, were enrolled. Early morning serum cortisol was performed. Subjects with a serum cortisol of v400 nmol?L -1 had a tetracosactrin stimulation test.Fifty subjects of mean age 13.1 yrs were treated with a mean dose of 924.7 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 35 publications
1
32
1
5
Order By: Relevance
“…The data from the current study of adrenal suppression in 20.8% of asthmatic children on mild and moderate doses of budesonide are in general agreement with the literature. The present authors do not know whether these children would present symptomatic adrenal insufficiency if they were treated with much larger doses of budesonide, such as children on large doses of fluticasone who reportedly experienced adrenal crisis [7][8][9][25][26][27]]. …”
Section: Discussionmentioning
confidence: 99%
“…The data from the current study of adrenal suppression in 20.8% of asthmatic children on mild and moderate doses of budesonide are in general agreement with the literature. The present authors do not know whether these children would present symptomatic adrenal insufficiency if they were treated with much larger doses of budesonide, such as children on large doses of fluticasone who reportedly experienced adrenal crisis [7][8][9][25][26][27]]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of airway eosinophilia potentially provides evidence that can help to optimise the dose and improve the delivery of inhaled steroids. This is important as inappropriately high-dose inhaled steroids may have significant side-effects, including severe hypoglycaemia [27], along with possible adverse effects on alveolar development [28].…”
Section: Investigations In Preschool Wheezers S Saglani Et Almentioning
confidence: 99%
“…The effects of ICS depend on the type of the drug, the dose, and the amount of drug that is absorbed [9]. A study by Sim et al, 2003, suggested that high-dose ICS can induce adrenal suppression in children with BA [45]. In 2004 Mohn et al, published a research, suggestng that also low dose ICS treatments are associated with the adrenal axis suppression [30].…”
Section: Resultsmentioning
confidence: 99%